A comparison of microbial community composition in two alpine springs in southern Nevada - Shawna Hunnicutt; El Hachemi Bouali; Bryan Sigel (PLoS ONE, 2026)
Springs are intersections between the geosphere and hydrosphere where localized ecosystems form. Microbial communities play important roles in these aquatic ecosystems and can be identified using environmental DNA (eDNA) acquisition and amplification techniques. The Spring Mountain range west of Las Vegas, Nevada is a sky island with over 300 naturally flowing cold water springs. eDNA was acquired at three sampling sites at two springs from different elevations on the eastern side of the range–Harris Spring (HS) located at 1,779 m elevation and Deer Creek Spring (DCS) located at 2,778 m elevation–to compare microbial community composition, abundance, alpha diversity, and median evenness. Aquatic chemistry parameters such as water temperature, pH, conductivity, total dissolved solids (TDS), sodicity, alkalinity, and dissolved oxygen were measured to quantify environmental conditions within the springs. Results show that DCS exhibited greater microbial abundance, alpha diversity, and median evenness when compared to HS. This differs from elevational diversity gradient expectations which predicts lower abundance, alpha diversity, and median evenness due to harsher environmental conditions and scarcer resources. Aquatic chemistry measurements indicated no significant difference in pH and dissolved oxygen between the two springs, and differences in water temperature and conductivity do not provide a substantive explanation for microbial community patterns observed. A discussion of other environmental variables that were observed to qualitatively differ between the study sites, such as exposure to solar radiation, stream reemergence, and anthropogenic disturbance, are offered as potential explanatory variables that warrant further investigation. Further research is needed to better quantify these relationships, which would also assist in the environmental conservation efforts of these fragile spring ecosystems.